On Nonunique Fixed Point Theorems via Interpolative Chatterjea Type Suzuki Contraction in Quasi-Partial b-Metric Space. (13th April 2022) - Gautam, Pragati; Singh, Shiv Raj; Kumar, Santosh; Verma, Swapnil
Abstract : In the present research paper, Chatterjea type contraction is defined and discussed in the framework of quasi-partial b-metric space. Further, some common fixed point results are proved using the notion of interpolation. The results are extended to fixed point theorems for modified Chatterjea type Suzuki contraction using w-admissible maps. The results proved are new and unique supported by application which will enrich the existing literature.